The Influence of Work Culture and Work-Life Balance on Workforce Agility in Cleaning Service Companies - Purwanto, Hendi; Damanik, Tigor Reinhard (Lentera Ilmu Nusantara, 2024)
This study aims to analyze the influence of work culture and work-life balance on workforce agility in cleaning service companies in Jakarta. In an industry context that often faces high pressure, a positive work culture plays an important role in improving employee performance. This study uses a quantitative method with the population of cleaning service employees who have worked for at least one year, involving 97 respondents. The results of the analysis show that work culture does not have a significant influence on labor agility, while work-life balance is proven to have a positive and significant effect. These findings indicate that work-life balance contributes more to the workforce's ability to adapt to change, especially in a dynamic work environment. Practical recommendations from the study include the importance of companies prioritizing policies that support work-life balance, such as flexible working hours and wellbeing programs, to improve workforce responsiveness to changing customer needs. This research is expected to provide insight for company management in creating effective strategies to improve organizational performance and employee welfare.